Trajectories of Digital Prenatal Service Utilization and Pregnancy Outcomes: A Multitrajectory Analysis - Alison K. Brinson, MSPH; Hannah R. Jahnke, PhD; Lily Rubin-Miller, MPH; Natalie Henrich, PhD, MPH; Bhavna Challa, BA; Christa Moss, PhD; Neel Shah, MD, MPP; Alex Peahl, MD, MSc (Mayo Clinic Proceedings: Digital Health, 2023)
Objective: To identify trajectories of prenatal digital service utilization across pregnancy and examine their associations with pregnancy outcomes. Patients and Methods: Data were extracted from 5409 pregnant people enrolled in Maven, a comprehensive digital platform for women’s and family health, between January 1, 2020, and May 27, 2022. Multitrajectory modeling used digital service utilization data (eg, articles read, classes attended, and appointments with providers) at each trimester to identify trajectories of digital use across pregnancy. Multinomial logistic regression models tested for associations between the utilization trajectories and user-reported pregnancy education, experiences, and outcomes. Results: Four distinct trajectories of digital service utilization were identified and labeled as follows: (1) baseline users (52% of users), (2) just-in-timers (16%), (3) learners (26%), and (4) super users (6%). Users varied across trajectories by race, perinatal support interests, mental health, and parity. Compared with baseline users, trajectories reflective of more digital health service utilization were all positively associated with self-reported influence of Maven on pregnancy education, maternity care experience, and clinical outcomes. Conclusion: Distinct trajectories of digital health utilization emerged among pregnant individuals with differences in user characteristics and medical risks by trajectory group. Users in higher-use trajectories reported greater benefits from digital health. These findings may be used to inform gaps in existing prenatal care and help provide tailored services to reflect the unique needs of each individual pregnancy.